AI Use among Undergraduate Students in Nepal: A Transformative Learning Perspective - Subba, Ganga; Adhikari, Devendra; Sharma, Laxmi; Neupane, Joshan (Punyawati Journal, 2026)
Artificial intelligence (AI) is reshaping higher education through personalised and learner-centered approaches; however, little is known about its transformative impact on students’ learning perspectives in developing contexts such as Nepal. This qualitative narrative inquiry explores the lived experiences of four first-semester Computer Science and Information Technology (CSIT) students from four colleges in Lalitpur. Data were analysed thematically using Braun and Clarke’s (2006) framework. The findings reveal three major themes: AI as a catalyst for perspective transformation; negotiating trust, ethics, and dependency; and contextual conditions shaping AI-enabled learning. While AI fosters learner autonomy and confidence, students critically navigate issues of accuracy, over-reliance, and ethical use. Structural factors, including digital infrastructure and affordability, significantly influence adoption and outcomes. The study concludes that AI can support transformative learning when implemented ethically and contextually, emphasizing the need for teacher up skilling, clear policy frameworks, and collaborative efforts to ensure equitable and human-centered integration.